Prognostic Value of Metastatic Tumoral Caveolin-1 Expression in Patients with Resected Gastric Cancer. (30th July 2017) - Sun, Der Sheng; Hong, Soon Auck; Won, Hye Sung; Yoo, Su Hyun; Lee, Han Hong; Kim, Okran; Ko, Yoon Ho
Abstract : Objective . Caveolin-1 (Cav-1), as the main component of caveolae, has complex roles in tumourigenesis in human malignancies. We investigated Cav-1 in primary and metastatic tumor cells of gastric cancer (GC) and its association with clinical outcomes. Methods. We retrieved 145 cases of GC who had undergone curative gastrectomy. The expression levels of Cav-1 was evaluated by immunohistochemistry, and its association with clinicopathological parameters and patient survival was analyzed. Results. High expression of Cav-1 protein of the GC in the stomach and metastatic lymph node was 12.4% (18/145) and 16.5% (15/91). In the multivariate analysis, tumoral Cav-1 protein in metastatic lymph node showed prognostic significance for relapse-free survival (RFS, HR, 3.934; 95% CI, 1.882–8.224; P = 0.001 ) and cancer-specific survival outcome (CSS, HR, 2.681; 95% CI, 1.613–8.623; P = 0.002 ). Among the GCs with metastatic lymph node, it remained as a strong indicator of poor prognosis for RFS (HR, 3.136; 95% CI, 1.444–6.810; P = 0.004 ) and CSS (HR, 2.509; 95% CI, 1.078–5.837; P = 0.032 ). Conclusion. High expression of tumoral Cav-1 protein in metastatic lymph node is associated with unfavorable prognosis of curative resected GC, indicating the potential of novel prognostic markers.